2012
DOI: 10.1183/09031936.00125312
|View full text |Cite
|
Sign up to set email alerts
|

Lung clearance index in adult cystic fibrosis patients: the role of convection-dependent lung units

Abstract: We investigated the extent of convective ventilation heterogeneity contributing to the observed lung clearance index values in adult cystic fibrosis patients, as the result of two simulated scenarios, either 1) a fixed part of the lungs becoming increasingly less compliant, or 2) an increasingly greater part of the lung being less compliant.In 25 cystic fibrosis patients and 25 matched controls, we computed the lung clearance index and also quantified curvilinearity of the washout concentration curve, where cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 29 publications
6
48
0
Order By: Relevance
“…AL-KHATHLAN et al [76] showed that the LCI correlates with indices of hyperinflation obtained by plethysmography in CF children. These data are in line with previous findings in adult CF patients suggesting that the LCI depends on airway dead-space [77]. Using data from a previous randomised controlled trial that had detected a treatment response from hypertonic saline inhalation in patients with mild CF lung disease [78], RATJEN et al volume, may provide a complementary outcome to the LCI in clinical trials.…”
Section: Lung Functionsupporting
confidence: 87%
“…AL-KHATHLAN et al [76] showed that the LCI correlates with indices of hyperinflation obtained by plethysmography in CF children. These data are in line with previous findings in adult CF patients suggesting that the LCI depends on airway dead-space [77]. Using data from a previous randomised controlled trial that had detected a treatment response from hypertonic saline inhalation in patients with mild CF lung disease [78], RATJEN et al volume, may provide a complementary outcome to the LCI in clinical trials.…”
Section: Lung Functionsupporting
confidence: 87%
“…Total washout duration was abbreviated, and intratest variability was lower. Abbreviated MBW protocols potentially improve success rates, especially in patients with severe lung disease or patients with brief attention spans (20)(21)(22). However, there is a decrease in sensitivity to detect treatment differences associated with these abbreviated MBW protocol LCIs (23).…”
Section: Lung Clearance Index Cutoff Valuesmentioning
confidence: 99%
“…From three acceptable tests, data were cumulated to obtain plots of mean expired concentration and phase III slope versus lung turnover (TO; cumulative expired volume/FRCmbw for any given test). From the semi-log plot of mean expired concentration (as a percent of initial concentration) versus TO we derived: 1) LCI, as the TO value corresponding to the intercept between the semi-log plot of mean expired concentration and the 1/0.40th initial concentration level; 2) Curv, as unity minus the ratio of two regression slopes, where the regression slope in the denominator is that determined in the range TO=0 and TO=LCI/2 and in the numerator that between TO=LCI/2 and TO=LCI [12]. From the plot of normalised phase III slope (normalised by mean expired concentration) versus TO, we derived indices of acinar and conductive (Sacin, Scond) ventilation heterogeneity, as well as two modified indices (Sacin*, Scond*) for use in patient groups such as CF where ventilation heterogeneity is so marked that Scond becomes invalid [22].…”
Section: Mbw Testmentioning
confidence: 99%
“…On the ventilation distribution side, indices of acinar and conductive (Sacin, Scond) ventilation heterogeneity derived from the normalised phase III slope analysis of the multiple-breath washout (MBW) have been used to characterise bronchial hyperresponsiveness in asthma [8] or asthma control [9], or to pick up different stages of smoking-induced lung disease [10]. In more severe lung disease such as in patients with COPD or patients with CF, the lung clearance index (LCI) [11] and the curvilinearity (Curv) derived from the MBW concentration curve [12] may suffice to quantify degree of heterogeneity. Airway resistance is also seen to be increased in asthma and COPD, with values depending on the method (forced oscillation or plethysmography) [13] or the equipment used [14].…”
Section: Introductionmentioning
confidence: 99%